2015
DOI: 10.1007/s00586-015-4143-3
|View full text |Cite
|
Sign up to set email alerts
|

Photographic measurement of head and cervical posture when viewing mobile phone: a pilot study

Abstract: Photogrammetry is a reliable, quantitative method to evaluate the head and cervical posture during mobile phone use. Compared to neutral standing, subjects display a more forward head posture when viewing the mobile phone screen, which is correlated with neutral posture, gaze angle and gender. Future studies will be needed to investigate a dose-response relationship between mobile phone use and assumed posture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 26 publications
0
58
0
4
Order By: Relevance
“…Guan and Fan [87] used photogrammetry to study 186 Chinese adults and found that head tilt angle increased and neck tilt angle decreased significantly during mobile phone viewing. Straker and Burgess-Limerick [88] stated that an increase in cervical muscle activity is evident with lower display placement when using electronic products.…”
Section: Discussionmentioning
confidence: 99%
“…Guan and Fan [87] used photogrammetry to study 186 Chinese adults and found that head tilt angle increased and neck tilt angle decreased significantly during mobile phone viewing. Straker and Burgess-Limerick [88] stated that an increase in cervical muscle activity is evident with lower display placement when using electronic products.…”
Section: Discussionmentioning
confidence: 99%
“…Digital photography was applied to assess body posture of children carrying heavy backpacks [86], to evaluate the quality of posture while standing [87, 88] and siting [89], or for quantifying the foot shape [90]. Several studies described usefulness of the photographic technique to assess patients with idiopathic scoliosis [75, 9194]. …”
Section: Discussionmentioning
confidence: 99%
“…This method makes use of the neck angle measured from a side view photo of a person. This method has been proven to be reliable ; therefore, in this paper, we used this method to validate the neck angle calculated from our smartphone monitoring system.…”
Section: Experiments and Demonstrationmentioning
confidence: 99%
“…Then, the system uses these two attributes, namely the tilt angle and the face angle, to calculate the neck angle based on the proposed neck angle calculation formula. Later in this paper, we evaluate the proposed algorithm and formula by conducting an experiment on 30 human subjects to compare the neck angle from our proposed smartphone‐based system with the previously published photogrammetric method . The evaluation was done using a statistical analysis to calculate the mean differences in the results from these two methods.…”
Section: Introductionmentioning
confidence: 99%